Pengaruh Implementasi Nucleus (Inti) terhadap Pertumbuhan Mutiara Diperairan Palabusa Kecamatan Lea-lea - Mujuna Hutuala; Veni Rosnawati; Ridwan Ridwan (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the potential of the waters of South Palabusa, Buton, as an ideal habitat for pearl oyster cultivation. This region has ecological advantages that can support the growth of oysters producing high-value pearls. However, pearl production is still strongly influenced by the application of nucleus implantation techniques and the condition of the aquatic environment. Therefore, this study aims to determine the effect of nucleus implantation on pearl growth and quality and identify environmental factors that play a significant role. The research method used is descriptive quantitative, with subjects being Pteria penguin oysters cultivated by the local community for a period of one month. The main parameters observed included the oyster survival rate, pearl size growth, and the quality of the resulting nacre. The findings provide valuable insight into how nucleus implantation can optimize pearl farming practices. The results showed that oysters implanted with nucleus implants had a survival rate of between 85–90%. Pearl diameter growth reached 1–2 cm per month, with a thicker nacre layer and brighter color than oysters without nuclei. Environmental factors, such as water temperature of 28–30°C, salinity of 30–35 ppt, pH 7.5–8.5, moderate water currents, and high plankton availability, have been shown to support successful cultivation. These environmental factors act as natural enhancers that improve pearl quality and survival rates. The findings of this study imply that the application of appropriate nucleus implantation techniques, accompanied by good environmental management, can increase pearl yield and quality. This not only provides significant economic benefits for cultivators but can also serve as a basis for developing sustainable pearl cultivation strategies in potential Indonesian waters. Thus, sustainable pearl aquaculture can become a promising sector for local communities.